Contemporary research methods and data analytics in the news industry - Gibbs, William J.; McKendrick, Joseph; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This book highlights the research behind the innovations and emerging practices being implemented within the journalism industry by focusing on key topics in social media and video streaming as a new form of media communication for collecting information and drawing conclusions about the current and future state of print and digital news"--Provided by publisher.
When journalism met the internet: old media and new media greet the online public / Mike Dillon -- Computational journalism: shaping the future of news in a big data world / Lady Dhyana Ziegler -- Research methods, data, and analytics: examining service design and user experience in TV- and newspaper-oriented digital news interfaces / William J. Gibbs, Ronan S. Bernas -- A tale of two newsrooms: how market orientation influences web analytics use / Patrick Ferrucci, Edson C. Tandoc Jr. -- Data-driven information consumption: heralding a new "golden age" of journalism and content creation? / Joseph E. McKendrick -- Web 2.0 and News 2.0: utilizing real-time analytics for modern news organizations / Kyle Gibson, Greg Gomer -- Shaping content strategies with user analytics and identities: how user analytics is shaping editorial strategy, driving marketing, and generating new revenue / Tricia Syed -- Big data, text mining, and news content: where is the big data? / Debora Cheney -- Using market research as the basis for successful content product decisions / Judith Durgin Pilla, Louis Pilla -- Research methodologies, data collection, and analysis at MailChimp: a case study / Gregg Bernstein, Laurissa Wolfram-Hvass -- Spreading the news: spreadable media, social networking, and the future of news production / Robert J. Baron -- Visualizing social network influence: measurement and case studies / Jeremy Harris Lipschultz -- The disruptive impact of emerging technology / Gordon J. Murray -- Transformational content and relationships: research, analytical tools, and big data in shaping the news user experience (UX) / Stuart Schwartz.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 07/21/2015).
Keywords: Journalism -- Research; Data mining; Big data; Broadcast journalism; Computational journalism; Computer-mediated communication; Data scraping; Digital media; News media; Social media; Text mining; User experience; Electronic books